Pharmacoeconomic analysis of using belimumab for the treatment of systemic lupus erythematosus - A. G. Tolkushin; N. L. Pogudina (IRBIS LLC, 2018)
The aim is to study the clinical and economic aspects of using belimumab for the treatment of systemic lupus erythematosus (SLe) in patients with high SLe activity, the presence of anti-DNA, a low level of complement in the blood plasma and minimal lupus organ damage at the early stage.Materials and methods. The Markov model of SLe is used. The initial probabilities of the Markov transitions are obtained from analysis of published clinical and observational studies. The prices of the relevant drugs were obtained from the VeD price registry. Medical and nonmedical expenses are calculated on the basis of the current standards for financial costs and coefficients, as well as payments for temporary and permanent disability. Indirect costs are calculated using the method of human capital.Results. It has been found that using belimumab leads to a decrease in costs (both direct and indirect), as well as an increase in patient survival. The total costs for belimumab vs standard therapy approximated 8.84 million rubles vs 17.72 million rubles (of which 4.05 million rubles vs 5.58 million rubles were direct costs, and 2.57 million rubles vs 2.88 million rubles were indirect medical costs) on average per patient in the belimumab group vs standard therapy group, respectively.Conclusion. The use of belimumab in the target population of patients is pharmacoeconomically justified and expedient because it leads to increased treatment efficiency and reduction of direct and indirect costs.